2019
DOI: 10.1002/ange.201912844
|View full text |Cite
|
Sign up to set email alerts
|

Surface‐Polarity‐Induced Spatial Charge Separation Boosts Photocatalytic Overall Water Splitting on GaN Nanorod Arrays

Abstract: Photocatalytic overall water splitting has been recognized as a promising approach to convert solar energy into hydrogen. However, most of the photocatalysts suffer from low efficiencies mainly because of poor charge separation. Herein, taking a model semiconductor gallium nitride (GaN) as an example, we uncovered that photogenerated electrons and holes can be spatially separated to the nonpolar and polar surfaces of GaN nanorod arrays, which is presumably ascribed to the different surface band bending induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 57 publications
0
10
0
Order By: Relevance
“…These results showed that the delocalized π-conjugated system with the amino group is more conducive to photodegradation of MO. It is reported that the electron-donating group can induce HOMO-LUMO electronic transitions that cause a change in the dipole moment, which results in effective separation of photogenerated charges (Belviso et al, 2019; Li et al, 2020 ). Therefore, it is notable that the catalytic efficiency followed the order of NH 2 -Phen/TiO 2 > NO 2 -Phen/TiO 2 > Phen/TiO 2 , which indicates that −NH 2 has a strong electron-donating group than −NO 2 .…”
Section: Resultsmentioning
confidence: 99%
“…These results showed that the delocalized π-conjugated system with the amino group is more conducive to photodegradation of MO. It is reported that the electron-donating group can induce HOMO-LUMO electronic transitions that cause a change in the dipole moment, which results in effective separation of photogenerated charges (Belviso et al, 2019; Li et al, 2020 ). Therefore, it is notable that the catalytic efficiency followed the order of NH 2 -Phen/TiO 2 > NO 2 -Phen/TiO 2 > Phen/TiO 2 , which indicates that −NH 2 has a strong electron-donating group than −NO 2 .…”
Section: Resultsmentioning
confidence: 99%
“…5 The electric fields in the near-surface space charge regions influence the spatial charge distribution by promoting the charge separation and accumulating electrons and holes on the two end surfaces perpendicular to the electric field, [6][7][8][9][10][11] resulting in super photocatalytic activities and enhanced sensitivity, with relevance to a wide range of applications in catalysis, photocatalysis, gas sensing, piezoelectronics and magnetoresistive devices. [12][13][14][15][16][17][18][19] Compared with non-polar surfaces, polar surfaces of nanocrystals usually have higher energy and therefore they are thermodynamically unstable. To minimize the energy of the systems, these polar surfaces tend to diminish and even vanish during the growth process, producing nanocrystals dominated by thermodynamically stable surfaces with low surface energy.…”
Section: Znsmentioning
confidence: 99%
“…Moreover, the quantum efficiency enhanced dramatically from 0.9% for the GaN thin-lm to 6.9% for the GaN nanorod arrays. 40 Zhang et al also experimentally conrmed that multi-eld coupling in KNbO 3 nanostructures could enhance its catalytic performance owing to the polarizationmodulated built-in electric elds, which effectively separated excited electron/hole pairs. The photocurrent density enhanced obviously from 25% for the nanocube counterpart to 55% for the KNbO 3 nanosheets.…”
Section: Introductionmentioning
confidence: 99%